Lifestyle determinants of diabetes mellitus amongst people living with HIV in the Eastern Cape province, South Africa - Nokwanda E. Bam; Wezile Chitha; Jafta Ntsaba; Sibusiso C. Nomatshila; Teke Apalata; Sikhumbuzo A. Mabunda (African Journal of Primary Health Care & Family Medicine, 2022)
Background: Type 2 diabetes mellitus (DM) has serious consequences for those affected. Little is documented on the lifestyle determinants of type 2 DM in people living with human immunodeficiency virus (PLWHIV).